The Role of Academic Motivation with Emotional Intelligence in Late Adolescence - Agrasvinta Midori Marbun; Estevania Tricia; Hanna Christina Uranus (PT Publikasiku Academic Solution, 2024)
The rise of digital technology has significantly affected the mental health of late adolescents, particularly through issues like cyberbullying and loneliness, which can adversely affect their academic motivation. Understanding the factors that contribute to academic success is crucial in addressing these challenges. This study aims to examine the role of emotional intelligence as a predictive factor for academic motivation among late adolescents in higher education. A quantitative approach was employed, utilizing an online questionnaire distributed to 250 college students. Data were analyzed using linear regression to assess the relationship between emotional intelligence and academic motivation. The findings reveal a significant positive correlation between emotional intelligence and academic motivation, with a coefficient of determination (R²) of 0.301. This indicates that emotional intelligence accounts for approximately 30.1% of the variance in academic motivation. The study concludes that higher emotional intelligence is associated with increased academic motivation among late adolescents. These findings underscore the importance of fostering emotional intelligence in educational settings to enhance student motivation and overall academic performance.